2017
DOI: 10.1177/1076029616686421
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Antithrombotic Therapy in Older Patients in Aged Care Facilities With Atrial Fibrillation

Abstract: Oral anticoagulants are essential drugs for the prevention of thromboembolic events in patients with atrial fibrillation (AF). Anticoagulants are, however, commonly withheld in older people due to the risk and fear of hemorrhage. Although the underutilization of anticoagulants in patients with AF has been demonstrated internationally, few studies have been conducted among aged care residents. The aim of this study was to determine the utilization of anticoagulants among people with AF residing in aged care fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Underutilization of anticoagulant therapy of these eligible high-risk patients was observed in our study. This finding is in line with the China 15 and International 16 19 studies reporting that anticoagulants are commonly underutilized in AF patients. Antiplatelet therapy cannot be recommended for stroke prevention in NVAF patients.…”
Section: Discussionsupporting
confidence: 90%
“…Underutilization of anticoagulant therapy of these eligible high-risk patients was observed in our study. This finding is in line with the China 15 and International 16 19 studies reporting that anticoagulants are commonly underutilized in AF patients. Antiplatelet therapy cannot be recommended for stroke prevention in NVAF patients.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, most PCPs did not provide adequate levels of education to NVAF patients. The latest studies have shown that among patients with NVAF, NOAC is superior to warfarin for the prevention of AF-related strokes [19]. However, we found that 81.39% of PCPs did not know of NOAC therapy because most PCPs in the community did not have a good understanding of the literature, despite having a positive attitude toward acquiring such knowledge.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, most PCPs did not provide adequate levels of education to NVAF patients. The latest studies have shown that among NVAF patients, the newer OAC is superior to warfarin for the prevention of AF-related strokes [22] . However, we found that 81.39% of PCPs did not know of the In the multiple linear regression analysis, the PCPs' knowledge score was related to their years of practice, whether they were in outpatient service, and their type of CHS center.…”
Section: Discussionmentioning
confidence: 99%